2004
DOI: 10.1161/01.res.0000143901.37063.2f
|View full text |Cite
|
Sign up to set email alerts
|

Passive Stiffness Changes Caused by Upregulation of Compliant Titin Isoforms in Human Dilated Cardiomyopathy Hearts

Abstract: In the pathogenesis of dilated cardiomyopathy, cytoskeletal proteins play an important role. In this study, we analyzed titin expression in left ventricles of 19 control human donors and 9 severely diseased (nonischemic) dilated cardiomyopathy (DCM) transplant-patients, using gel-electrophoresis, immunoblotting, and quantitative RT-PCR. Both human-heart groups coexpressed smaller (approximately 3 MDa) N2B-isoform and longer (3.20 to 3.35 MDa) N2BA-isoforms, but the average N2BA:N2B-protein ratio was shifted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
251
2
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(285 citation statements)
references
References 33 publications
24
251
2
8
Order By: Relevance
“…This probably reflects a compensatory effect of titin isoform expression. Consistent with previous studies [15,16], samples from failing hearts had a greater relative content of the large N2BA isoform of titin (p=0.047, Figure S3B). This isoform shift tends to decrease passive stiffness and seems to counteract the mechanical effect of increased fibrosis in the samples from the failing hearts.…”
Section: Failing Hearts Have Increased Mid-myocardial Fibrosissupporting
confidence: 90%
“…This probably reflects a compensatory effect of titin isoform expression. Consistent with previous studies [15,16], samples from failing hearts had a greater relative content of the large N2BA isoform of titin (p=0.047, Figure S3B). This isoform shift tends to decrease passive stiffness and seems to counteract the mechanical effect of increased fibrosis in the samples from the failing hearts.…”
Section: Failing Hearts Have Increased Mid-myocardial Fibrosissupporting
confidence: 90%
“…The somewhat stronger increase of N2BA expression compared with N2B in our IUGR rats together with the significantly elevated values of LVEDD and LVESD in these animals supports the hypothesis of a more distensible myocardium post-IUGR. According to this, an overexpression of N2BA could be found in the myocardium of patients with dilated cardiomyopathy (23).…”
Section: Impaired Myocardial Performance and Iugrmentioning
confidence: 74%
“…These gels showed that the T1 mobility varied greatly between skeletal and cardiac muscles from different mammals TrombitĂĄs et al 2000;Neagoe et al 2003;Warren et al 2003a, b;Lahmers et al 2004;Makarenko et al 2004;Udaka et al 2008;Guo et al 2013). The major T1 bands were ascribed to the titin isoforms N2B and N2BA in cardiac muscle and the titin isoform N2A in skeletal muscles.…”
Section: Electrophoretic Detection Of Titin Isoformsmentioning
confidence: 95%